Changes in water quality following gypsum application to catchment soils of the Mount Lofty Ranges, South Australia - Varcoe, J.; van Leeuwen, J.; Chittleborough, D.; Cox, J.; Smernik, R.; Heitz, Anna (Elsevier Science, 2010)
The impacts of gypsum application to pasture on the concentration and character of dissolved organic carbon (DOC) and on the inorganic profile of surface and subsurface water were investigated in the Mount Lofty Ranges of South Australia. Two adjacent sub-catchments of the Mount Bold reservoir were selected for study, where gypsum was applied at a rate of 15,000 kg ha1 to one and the other left untreated, as a control. Gypsum amendment led to reductions in DOC concentrations in surface and subsurface flows of about 50%, significant increases in aqueous Ca, Mg, Mn and Na and lower concentrations of other metals (Al, Fe) due to Ca2+ exchange. Natural organic matter (NOM) in water from the gypsum treated site was found to have a lower relative aromaticity compared with the control. Alum treatment of control and gypsum-treated waters by a jar test procedure led to 73% and 48% removal of DOC, respectively, resulting in similar residual concentrations. This indicates that DOC removed by traditional alum treatment of drinking water supplies is also susceptible to in situ gypsum treatment, probably via a similar metal-catalysed aggregation mechanism. We conclude that gypsum application to soils of medium to heavy texture has potential to enhance their capacity to bind NOM, thereby lowering DOC concentrations in surface and subsurface flows.